2021
DOI: 10.3389/fgene.2021.738230
|View full text |Cite
|
Sign up to set email alerts
|

DNA Double Strand Break Repair Pathways in Response to Different Types of Ionizing Radiation

Abstract: The superior dose distribution of particle radiation compared to photon radiation makes it a promising therapy for the treatment of tumors. However, the cellular responses to particle therapy and especially the DNA damage response (DDR) is not well characterized. Compared to photons, particles are thought to induce more closely spaced DNA lesions instead of isolated lesions. How this different spatial configuration of the DNA damage directs DNA repair pathway usage, is subject of current investigations. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 127 publications
(221 reference statements)
0
10
0
Order By: Relevance
“…These and other aberrant DNA structures trigger a multifaceted network of DNA damage response signaling and lead to the subsequent removal of DNA lesions by various dedicated and complementary DNA repair processes [18,157]. These include amongst others homologous recombination (HR) and non-homologous end joining (NHEJ) for the repair of double-stranded DNA breaks [158], base excision repair (BER) for the removal of subtle base modifications [159], global genome-nucleotide excision repair (GG-NER) and transcription-coupled repair (TCR) for bulky helix distorting lesions [160], and interstrand crosslink (ICL) repair to resolve DNA crosslinks during replication [161] (Figure 2). Translesion synthesis polymerases can still bypass damaged DNA bases during replication giving rise to increased mutations over time [162].…”
Section: Conceptualization Of Chemotherapeutics Driving Segmental Agingmentioning
confidence: 99%
“…These and other aberrant DNA structures trigger a multifaceted network of DNA damage response signaling and lead to the subsequent removal of DNA lesions by various dedicated and complementary DNA repair processes [18,157]. These include amongst others homologous recombination (HR) and non-homologous end joining (NHEJ) for the repair of double-stranded DNA breaks [158], base excision repair (BER) for the removal of subtle base modifications [159], global genome-nucleotide excision repair (GG-NER) and transcription-coupled repair (TCR) for bulky helix distorting lesions [160], and interstrand crosslink (ICL) repair to resolve DNA crosslinks during replication [161] (Figure 2). Translesion synthesis polymerases can still bypass damaged DNA bases during replication giving rise to increased mutations over time [162].…”
Section: Conceptualization Of Chemotherapeutics Driving Segmental Agingmentioning
confidence: 99%
“…The full complexities of these pathways have been extensively reviewed elsewhere [ 5 , 6 ]. DSBs arise from both endogenous and exogenous sources, such as free radicals and ionizing radiation, respectively [ 7 , 8 ], as well as V(D)J recombination and class switch recombination (CSR) [ 9 , 10 ]. SSBs can be induced by ionizing radiation, reactive oxygen species (ROS), and as a result of replication errors resulting in single strand DNA (ssDNA) [ 11 , 12 ].…”
Section: The Dna Damage Responsementioning
confidence: 99%
“…Therefore, a large fraction of DSB induced by charged particles is still processed by c-NHEJ, similarly to X-rays. Some data show that mammalian cells resort more often to HR than NHEJ to process clustered DNA lesions ( Refs 46,47,48). Surprisingly, measuring DSB repair kinetics in repair-deficient cell lines, some authors found that after proton therapy (low-LET, similar to X-rays), there was an almost complete shift from NHEJ to HR (Refs 49, 50, 51).…”
Section: Dna Repair Pathwaysmentioning
confidence: 99%